2018
DOI: 10.1101/lm.046326.117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of separate components of training that contribute to long-term memory formation after learning that food is inedible in Aplysia

Abstract: Training with inedible food for a period that is too brief to produce long-term memory becomes effective in producing memory when training is paired with a nitric oxide (NO) donor. Lip stimulation for the same period of time paired with an NO donor is ineffective. Using qPCR, we examined molecular correlates of brief training versus lip stimulation, of treatment with an NO donor versus saline, and of the combined stimuli producing long-term memory. Changes were examined in mRNA expression of homologs of ,, ,, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…A number of previous reports have localized molecular correlates of memory formation to the buccal ganglia (Levitan et al 2008(Levitan et al , 2012Briskin-Luchinsky et al 2018), whereas we propose above that the effects of NO during training occur in the cerebral ganglion. It is possible that different aspects of memory are stored in different ganglia.…”
Section: Roles Of the Buccal And Cerebral Gangliamentioning
confidence: 50%
See 2 more Smart Citations
“…A number of previous reports have localized molecular correlates of memory formation to the buccal ganglia (Levitan et al 2008(Levitan et al , 2012Briskin-Luchinsky et al 2018), whereas we propose above that the effects of NO during training occur in the cerebral ganglion. It is possible that different aspects of memory are stored in different ganglia.…”
Section: Roles Of the Buccal And Cerebral Gangliamentioning
confidence: 50%
“…4). In addition, a previous study found that injecting behaving animals with an NO donor, which substitutes for attempts to swallow, causes increased expression of genes associated with memory consolidation, such as CREB1 and C/EBP, in the cerebral ganglion (Briskin-Luchinsky et al 2018).…”
Section: No In the Cerebral Ganglionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes in molecular correlates measured in the whole cerebral ganglia would not pick up changes localized to a small number of key neurons, such as the cholinoceptive command-like CBI neurons, leaving open the possibility that changes in the response to ACh may also underlie aspects of long-term memory. Previous reports (Briskin-Luchinsky et al 2018a) also found that treatment with an NO donor produces changes in the cerebral ganglion, and the NO donor applied to the cerebral ganglion inhibits CCh-induced motor programs (Briskin-Luchinsky et al 2018b), suggesting that the effects of NO on memory formation are localized to the cerebral ganglion.…”
Section: Aspects Of Memory Are Localized To a Postsynaptic Decrease Imentioning
confidence: 78%
“…Previous studies on molecular correlates of long-term memory formation showed increases after training in the buccal ganglia, but no changes in expression were found in the whole cerebral ganglion (Levitan et al 2008;Michel et al 2011;Briskin-Luchinsky et al 2018a). However, changes in molecular correlates measured in the whole cerebral ganglia would not pick up changes localized to a small number of key neurons, such as the cholinoceptive command-like CBI neurons, leaving open the possibility that changes in the response to ACh may also underlie aspects of long-term memory.…”
Section: Aspects Of Memory Are Localized To a Postsynaptic Decrease Imentioning
confidence: 89%